Enhanced Recovery After Surgery Protocol Optimizes Results and Cost of Laparoscopic Radical Nephrectomy - Chen, Siming; He, Zhiwen; Yao, Shijie; Xiong, Kangping; Shi, Jiageng; Wang, Gang; Qian, Kaiyu; Wang, Xinghuan (Frontiers in Oncology, 2022)
Background: The enhanced recovery after surgery (ERAS) is effective in surgical operations, but the effect of ERAS on laparoscopic radical nephrectomy (LRN) is unclear. This study is to evaluate the effectiveness of implementing the ERAS protocol in LRN. Methods: Renal cell carcinoma (RCC) patients, who received LRN in our hospital before ERAS implementation (February 1, 2019 to August 31, 2020) and after ERAS implementation (September 1, 2020 to September 30, 2021) were retrospectively analyzed. To evaluate and compare the impact of ERAS protocols on length of hospital stay (LOS), hospitalization expenses, and postoperative complications. Results: Total LOS and postoperative LOS were significantly shorter in ERAS group than in pre-ERAS group [15.0 (13.5-19.5) vs. 12.0 (10.0-14.0), P < 0.001; 8.0 (7.0-10.0) vs. 7.0 (5.0-8.8), P = 0.001]. Compared with the pre-ERAS group, the hospitalization expenses of the ERAS group were also lower (p = 0.023). In addition, the incidence of postoperative complications in the ERAS group also decreased (p = 0.054). Conclusions: The application of ERAS protocol in LRN could help reduce postoperative complications, accelerate patient recovery and reduce hospitalization costs. This protocol is safe and effective, worthy of clinical promotion.